KONSTRUKSI IDEOLOGI BAHASA GURU DALAM PEMBELAJARAN DI KELAS - Ribut Wahyu Eriyanti (LITERA, 2014)
This study aims to describe the construction and strategy of ideology expressions represented by the teacher language in classroom learning. It employed the critical qualitative approach through Critical Discourse Analysis. The data were collected through observations of learning in public and private junior high schools in Malang City. The findings are as follows. First, ideologies represented by the teacher language include: (a)students as the teacher’s subordinates, (b) the teacher as controller of students, (c) silence as the best way in learning, (d) students’ mistakes as taboos, (e) obedience as a success determinant, (f) differences in learning capabilities between males and females, (g) students possessing no autonomy and responsibility, (h) students’ obligation to serve the teacher,(i) students that need to be scared in order to learn, and (j) students’ basic tendency to lie. Second, such ideologies are expressed through the use of prohibition, command, words ideologically contested, lexicalization, irony, metaphor, eponym, and labeling.